Epidemiological Study of the Incidence of Cancers Eligible for Proton or Carbon Ions Therapy: Methodology and Results of Recruitment Estimation. (20th June 2013) - Patin, Stéphanie; Pommier, Pascal; Yi, Hu; Baron, Marie Hélène; Balosso, Jacques
Abstract : Context . Hadrontherapy is an innovative form of radiotherapy using beams of protons or carbon ions able to destroy some radio-resistant tumours. Because these tumours are highly specific amongst all cancerous tumours, it is impossible to determine the incidence of these diseases from surveillance registries. Goal . To assess, within the Rhône-Alpes region, the incidence of cancers being hadrontherapy indications. Method . Prospective, multicentre continuous data collection during 1 year, by practitioners participating to multidisciplinary tumor board. Tumours are inoperable, radio resistant, at primary stage of development, or locally recurrent, with low metastatic potential. Results . Study involved 27 healthcare centres, 52 groups of specialist practitioners. The estimated incidence of cancers eligible for hadrontherapy in the Rhône-Alpes region in 2010, that is, for 34 locations in all, is of 8.5/100 000 inhabitants. Appraisal of the low potential of metastatic progression is impeded, because these are rare diseases, whose outcome is unfamiliar to investigators. Conclusion . Future epidemiological studies will need to focus on prognosis and on the metastatic progression rate of these diseases. Indeed, there are few information available on this subject in the literature that could be used to improve preventive measures, medical care, and the surveillance of these rare cancers.